Advertisements
Advertisements
प्रश्न
If p(y) = 2y3 − 6y2 − 5y + 7 then find p(2).
उत्तर
p(y) = 2y3 − 6y2 − 5y + 7
p(y) = p(2)
`∴ p(2) = 2 × (2)3 − 6 × (2)2 − 5 × 2 + 7`
= 2 × 8 − 6 × 4 − 10 + 7
= 16 − 24 − 10 + 7
= −11
APPEARS IN
संबंधित प्रश्न
If `p(y) =y^2 - 3sqrt2y + 1` then find `p (3sqrt 2)`.
Find the value of the polynomial 2x - 2x3 + 7 using given values for x.
x = -1
Find the value of the polynomial 2x − 2x3 + 7 using given values for x.
x = 0
For the following polynomial, find p(1), p(0) and p(-2).
`p(x) = x^3`
If `p(x) = 2x^2 - 5sqrt 3 x + 5` then `p(5 sqrt 3)`.
`p(x) = x^2 - 7 sqrt 7 x + 3 "then " p(7 sqrt 7) = ?`
When x = −1, what is the value of the polynomial 2x3 + 2x?
Find the value of the polynomial f(y) = 6y – 3y2 + 3 at y = 1
Find the value of the polynomial f(y) = 6y – 3y2 + 3 at y = 0
The sum of the polynomials p(x) = x3 – x2 – 2, q(x) = x2 – 3x + 1